2015
DOI: 10.1111/all.12729
|View full text |Cite
|
Sign up to set email alerts
|

Maternal nutrition during pregnancy and risk of asthma, wheeze, and atopic diseases during childhood: a systematic review and meta‐analysis

Abstract: Current evidence suggests a protective effect of maternal intake of each of three vitamins or nutrients (vitamin D, vitamin E, and zinc) against childhood wheeze but is inconclusive for an effect on asthma or other atopic conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
148
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(161 citation statements)
references
References 57 publications
3
148
2
2
Order By: Relevance
“…The authors postulated that the protective effects that were found only for wheeze may be through reduced susceptibility to viral infections. There was no association with asthma, eczema, or allergic rhinitis [19].…”
Section: Key Pointsmentioning
confidence: 81%
“…The authors postulated that the protective effects that were found only for wheeze may be through reduced susceptibility to viral infections. There was no association with asthma, eczema, or allergic rhinitis [19].…”
Section: Key Pointsmentioning
confidence: 81%
“…The levels of prenatal vitamin D on wheeze/asthma susceptibility in offspring have been extensively investigated in observational studies [49,50,91,92]. There are two meta-analyses that have shown high dietary vitamin D intake during pregnancy to be associated with a reduced risk of wheeze in the offspring (Nurmatov et al [91] OR 0.56, 95% CI 0.42-0.73; Beckhaus et al [92] OR 0.58, 95% CI 0.38-0.88).…”
Section: Prenatal Vitamin D Status and Asthma Riskmentioning
confidence: 99%
“…There are two meta-analyses that have shown high dietary vitamin D intake during pregnancy to be associated with a reduced risk of wheeze in the offspring (Nurmatov et al [91] OR 0.56, 95% CI 0.42-0.73; Beckhaus et al [92] OR 0.58, 95% CI 0.38-0.88). However, the results of metaanalysis from observational studies but based on maternal serum 25(OH)D concentrations on asthma/wheeze outcome are controversial yet.…”
Section: Prenatal Vitamin D Status and Asthma Riskmentioning
confidence: 99%
“…Regarding maternal diet during pregnancy, a small number of cohort studies have highlighted associations between wheezing in the first years of life and reduced maternal intake of vitamins E and D, zinc, and omega-3 PUFAs during pregnancy [11,21]. The few longitudinal studies conducted on associations between maternal dietary patterns during pregnancy and wheeze/asthma in the offspring reported, overall, no association [21].…”
Section: Diet and Asthma: Primary Preventionmentioning
confidence: 99%
“…The few longitudinal studies conducted on associations between maternal dietary patterns during pregnancy and wheeze/asthma in the offspring reported, overall, no association [21]. Regarding diet during childhood, few longitudinal studies have been published.…”
Section: Diet and Asthma: Primary Preventionmentioning
confidence: 99%